Delegating Disclosure and Production Choices - Bagnoli, Mark; Watts, Susan G. (The Accounting Review, 2015)
ABSTRACT We study how joint delegation of production and disclosure choices alters the incentives that firm owners offer to their managers. Our first set of results shows how the incentive weights that owners place on revenues are affected by firm characteristics and by whether their manager chooses ex ante voluntary disclosure. This arises because the owners choose how sensitive the manager's compensation is to her production choice and, because this sensitivity is naturally greater if the manager opts to disclose, owners substitute disclosure for direct contractual incentives. Owners also substitute a rival firm's disclosures for direct incentives. Finally, we show that joint delegation alters the information environment for competing firms by creating incentives to provide more information about the less aggressive competitor and less information about the more aggressive competitor. All of these effects are exacerbated in industries with less product differentiation.